A sucessão ecológica em ambientes florestais em restauração: estrutura e dinâmica da regeneração natural - Gonzaga, Luciana de Moura (2016)
Ecological restoration aims to restore the self-sustainability potential of degraded environments. The successional trajectory of areas in restoration may differ from the reference ecosystem on a number of factors, especially the disturbance history of the area and management techniques applied in order to reverse the degradation scenario. In this sense, the objective of this study was to characterize the dynamics of natural regeneration and the structure of the regenerating community in an area of ecological restoration for 25 years on the right bank of the Rio Grande in the Power Station in Camargos that belongs to the Companhia Energetica de Minas Gerais - CEMIG, Nazareno, MG, in order to identify the current state of environmental regeneration. In November 2014, there was the first community inventory of seedlings existing in regeneration subplots (2 x 2 m) within the inclusion criteria (height ≥ 10 cm and DBH <5 cm), divided into 44 subplots (11 plots) in two areas, one area in restoration (REF) and a fragment of native vegetation (FRAG). In October 2015, the second sampling was carried out, in which individuals were resampled and recruits and dead individuals quantified. The parameters abundance, floristic similarity, density, dominance, importance value, equability, richness and diversity were analyzed in both samples. The dynamics was evaluated for the number of individuals and basal area in the period of 2014-2015 and individuals distributed according to height. The history of usage area provoked different behavior between the study environments; the patterns of the FRAG and REF communities along the years allowed the distinction between environments and demonstrated great environmental diversity, with differences in the abundance of species, floristic similarity, richness, diversity, vertical structure and dynamics parameters. In the REF area, there was a considerable increase in the density of individuals along the years and the establishment of different species. In this sense, the evaluation of natural regeneration in REF has shown that resilience is gradually being resumed, a necessary condition to support the potential for environmental self-sustainability. However, given the disturbance history, it can be concluded that the environment moves to an alternative state, which is possibly different from that prior to degradation.